2022
DOI: 10.1590/1413-81232022276.17692021
|View full text |Cite
|
Sign up to set email alerts
|

Acolhimento integral em Centros de Atenção Psicossocial Álcool e Drogas na perspectiva da proteção dos direitos humanos

Abstract: Resumo Este artigo tem por objetivo avaliar se os resultados do acolhimento integral em Centros de Atenção Psicossocial Álcool e Drogas III (CAPS AD III) atendem aos padrões de qualidade para proteção e respeito dos direitos humanos dos usuários. Desenvolvemos um estudo avaliativo, quantitativo e de desenho longitudinal com 122 usuários acolhidos integralmente em dois CAPS AD III, com follow-up após 14 e 90 dias. Os resultados dos indicadores qualidade de vida, consequências da dependência de substâncias e rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Finally, in the fourth study, it was identified that the establishments partially met the quality standards for protection and respect for human rights but emphasized that being in the 24-hour reception improved the general health condition and well-being of users, reduced the severity of negative consequences resulting from the use of alcohol and other drugs and enabled changes for psychosocial rehabilitation and inclusion in the community. The challenges identified to achieve quality in guaranteeing human rights correspond to common issues experienced in the care of people who use drugs and live in situations of vulnerability, which benefit from the support of inclusive public policies (Boska et al, 2022).…”
Section: Evaluation Of Services Through the Qualiyrights Initiativementioning
confidence: 99%
“…Finally, in the fourth study, it was identified that the establishments partially met the quality standards for protection and respect for human rights but emphasized that being in the 24-hour reception improved the general health condition and well-being of users, reduced the severity of negative consequences resulting from the use of alcohol and other drugs and enabled changes for psychosocial rehabilitation and inclusion in the community. The challenges identified to achieve quality in guaranteeing human rights correspond to common issues experienced in the care of people who use drugs and live in situations of vulnerability, which benefit from the support of inclusive public policies (Boska et al, 2022).…”
Section: Evaluation Of Services Through the Qualiyrights Initiativementioning
confidence: 99%